Fabrication and investigations of kenaf fiber and banana fiber reinforced composite material. (2021) - Murugan, K.; Venkatesh, S.; Thirumalai, R.; Nandhakumar, S.
Abstract: The fuel efficiency and emission regulation of two wheels are two important issues in these days. The best way to increase the fuel efficiency without sacrificing safety is to employ fiber reinforced composite materials used for the two wheeler. In this study two wheeler mudguard which is used to protect the mud and rain water placed on front and rear wheel is considered for investigations. Mud guard is the one of the part having more weight and in this work, the existing steel mudguard is replaced with composite mudguard. The fabrication of composite mudguard made up of glass fiber with kenaf and banana reinforced polymer is carried out and the weight of the mudguard can be reduced. In this work, fabrication of mudguard with composite material is done and its weight percentage and hardness is calculated and analysed.